2004
DOI: 10.1242/dev.01213
|View full text |Cite|
|
Sign up to set email alerts
|

Metastasis-associated protein 1 deregulation causes inappropriate mammary gland development and tumorigenesis

Abstract: Emerging data suggest that metastasis-associated protein 1 (MTA1) represses ligand-dependent transactivation functions of estrogen receptor-alpha in cultured breast cancer cells and that MTA1 is upregulated in human breast tumors. However, the role of MTA1 in tumorigenesis in a physiologically relevant animal system remains unknown. To reveal the role of MTA1 in mammary gland development, transgenic mice expressing MTA1 under the control of the mouse mammary tumor virus promoter long terminal repeat were gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 45 publications
2
26
0
1
Order By: Relevance
“…Further- more, MTA3-induced hypobranching in the mammary gland is mechanistically linked with the direct corepressor activity of the MTA3-HDAC complex on Wnt4 chromatin. These effects of MTA3 are opposite those of MTA1 in virgin mammary gland (41). These findings support the notion of physiological differences among the MTA family members and underscore the lack of functional redundancy among individual MTA proteins.…”
Section: Mta1 In Mouse Mammarysupporting
confidence: 77%
See 1 more Smart Citation
“…Further- more, MTA3-induced hypobranching in the mammary gland is mechanistically linked with the direct corepressor activity of the MTA3-HDAC complex on Wnt4 chromatin. These effects of MTA3 are opposite those of MTA1 in virgin mammary gland (41). These findings support the notion of physiological differences among the MTA family members and underscore the lack of functional redundancy among individual MTA proteins.…”
Section: Mta1 In Mouse Mammarysupporting
confidence: 77%
“…Gland Development-A recent study showed that forced overexpression of MTA1 in the mouse mammary gland epithelium was accompanied by extensive ductal branching and proliferation in virgin glands, which was mechanistically linked to an altered ratio of progesterone receptor A and B isoforms (41). These data suggest a role for MTA1 in mammary gland development.…”
Section: Mta1 In Mouse Mammarymentioning
confidence: 98%
“…These mice also developed hyperplastic nodules and mammary tumors [40]. In this study, the underlying molecular mechanisms were also examined, and the results suggested that MTA1 dysregulation in mammary epithelium and cancer cells triggered down-regulation of the progesterone receptor-B isoform and up-regulation of the progesterone receptor-A isoform, resulting in the up-regulation of the progesterone receptor-A target genes Bcl-XL and cyclin D1 in mammary glands of virgin mice.…”
Section: Other Possible Functions Of Mta Proteins In Cancermentioning
confidence: 75%
“…This property is in contrast to MTA1-transgenic mice, where the inappropriate development of mammary glands results in the development of hyperplastic nodules and mammary tumors, including adenocarcinomas and lymphomas [8,40]. MTA3 also represses Wnt4 transcription and Wnt4 secretion, inhibiting Wnt-target genes in mammary epithelial cells.…”
Section: Repression Of the Transactivating Function Of Era By Mta Promentioning
confidence: 89%
See 1 more Smart Citation